2012
DOI: 10.1016/j.neuroscience.2012.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of delta opioid receptor-expressing neurons in the mouse hippocampus

Abstract: Delta opioid receptors participate to the control of chronic pain and emotional responses. Recent data also identified their implication in spatial memory and drug-context associations pointing to a critical role of hippocampal delta receptors. We examined the distribution of delta receptor-expressing cells in the hippocampus using fluorescent knock-in mice that express a functional delta receptor fused at its carboxyterminus with the green fluorescent protein in place of the native receptor. Colocalization wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 39 publications
2
52
0
Order By: Relevance
“…Nr AB2251, Millipore, Billerica, MA, USA, dilution 1:2000) and goat anti-choline acetyltransferase (ChAT) (Cat. Nr AB144, Millipore, Billerica, MA, USA, dilution 1:400) polyclonal antibodies have been largely used in the literature and in our laboratory (Erbs et al, 2012). Rat anti-Substance P (SP) monoclonal antibody (Cat.…”
Section: Methodsmentioning
confidence: 99%
“…Nr AB2251, Millipore, Billerica, MA, USA, dilution 1:2000) and goat anti-choline acetyltransferase (ChAT) (Cat. Nr AB144, Millipore, Billerica, MA, USA, dilution 1:400) polyclonal antibodies have been largely used in the literature and in our laboratory (Erbs et al, 2012). Rat anti-Substance P (SP) monoclonal antibody (Cat.…”
Section: Methodsmentioning
confidence: 99%
“…DORs are broadly expressed in the nervous system [14]. In the forebrain, a main site for the control of epileptic seizures [15], DORs are expressed in cortex and hippocampus with well-characterized expression in GABAergic neurons for hippocampus [16, 17]. …”
Section: Introductionmentioning
confidence: 99%
“…In the hippocampus, these receptors are mainly present in gamma-aminobutyric acid (GABA)ergic neurons of the DH, e.g. Ammon's horn and dentate gyrus [39], suggesting their involvement in neural plasticity. Moreover, it has recently been reported that Oprd1 2/2 mice display decreased ability to solve hippocampal-dependent tasks, e.g.…”
Section: Introductionmentioning
confidence: 99%